PENGARUH KIDS’ ATHLETICS TERHADAP SELF-ESTEEM DAN KEBUGARAN JASMANI (STUDI EXPOST FACTO PADA SISWA SEKOLAH ATLETIK PAJAJARAN) - Akbaruddin, Asep (STKIP Subang, 2018)
The purpose of this study to obtain empirical data on the effect of Kids' Athletics Against Self-Esteem And Physical Fitness in Athletic Pajajaran School students. The research methodology used Ex Post Facto casual- comparative design. Total sample of 30 students from elementary age group 11 -12 years in the School Athletic Padjadjaran Bandung taken by the sampling technique used nonprobability Sampling technique, using saturation sampling (total sampling). The instrument used was Hare Self-esteem Scale (HSS) developed by Bruce R. Hare (Kevin Corcoran and Joel Fischer, 2000: 550-552) and Indonesia Physical Fitness Test (TKJI) developed Ministry of Education (2003). From processing and analysis score that has been done, the result that; First off, Program Kids' Athletics have a significant influence on the Self-Esteem of Students in School Athletic Pajajaran. Secondly, Program Kids' Athletics have a significant influence on Physical Fitness Students in School Athletic Pajajaran.